PENGARUH SISTEM INFORMASI SDM DAN IKLIM ORGANISASI TERHADAP EFEKTIVITAS MANAJEMEN SDM DI BANK SYARIAH BUKOPIN - Saputra, Uun Endang; Budhijana, Raden Bambang (Journal of Accounting, Management and Islamic Economics, 2024)
The aim of this study is to determine if there is impact between the HR information system and the organizational climate, both individually and together, on the effectiveness of HR management at Bukopin Syariah Bank. This research was conducted using descriptive research methods and data processing using Structural Equation Modeling (SEM) techniques. Data collection techniques based on literature studies and field studies. The results of this study found that HR information systems and organizational climate, both individually and together, have a positive and significant effect on the effectiveness of HR management. This research recommends that Bank Syariah Bukopin conducts an assessment of the old HR information system and builds a reliable, effective and integrated HR information system as needed at Bank Syariah Bukopin. On the dimensions of rewards and sanctions that are of less value to the organizational climate variable, policy makers need to review and improve performance-based compensation and reward and punishment systems so that they are perceived to be fairer and ultimately expected to motivate employees to improve employee productivity and performance according to the set targets.